Major haemorrhage related to surgery in patients with type 1 and possible type 1 von Willebrand disease - Woods, Adriana Inés; Blanco, Alicia Noemí; Chuit, Roberto; Meschengieser, Susana Sara; Kempfer, Ana Catalina; Farías, Cristina Elena; Lazzari, María Angela (Thrombosis and Haemostasis, 2008)
Patients with von Willebrand disease (VWD) frequently bleed under a challenge. The aim of our study was to identify predictive markers of perioperative major haemorrhage in type 1 (VWF:RCo = 15–30 IU dl-1) and possible type 1 (VWF:RCo = 31–49 IU dl-1)VWD patients. We recorded perioperative bleeding complications previous to diagnosis and laboratory parameters in 311 patients with 498 surgical procedures. The patients were grouped according to the absence (A) or presence (B) of perioperative major haemorrhages. Eighty-one patients (26%) and 87 surgical procedures (17.5%) presented major haemorrhages associated with surgeries. There was no difference between the percentage of type 1 and possible type 1 VWD patients who had major haemorrhages (32.6% and 24.8% respectively; p=ns). No difference in the prevalence of O blood group, age, gender, positive family history and laboratory test results (FVIII and VWF) was observed, independent of the haemorrhagic tendency. Bleeding after tooth extraction was the most frequent clinical feature observed in patients with perioperative major haemorrhages. The bleeding score and the number of bleeding sites (≥3) were not predictors of major haemorrhage associated with surgery. Caesarean section and adenotonsillectomy showed the highest frequency of major haemorrhages (24.6% and 22.3%, respectively). In conclusion, type 1 and possible type 1VWD patients showed similar incidence of perioperative major haemorrhages. Laboratory tests and positive family history did not prove to be effective at predicting major haemorrhages in patients that had either type 1 or possible type 1 VWD. The history of bleeding after tooth extraction could define risk factors of major haemorrhage.
Keywords: Type 1 VWD; surgery; major haemorrhage; laboratory and clinical predictive markers